Employee Perceptions of the Performance Appraisal Process in a Hospitality Organisation in Namibia - Goliath, Marusca (School of Management Studies, 2023)
Performance appraisal is an essential tool for employee development and organisational success. The goal of performance management and performance appraisal is to help employees improve their skills and to find and address gaps in performance in the organisation. Employee perceptions of the fairness of performance appraisal determine the success and sustainability of the performance management system. Generally, employees are more accepting of performance appraisals when they perceive the process to be fair and developmental. This study aimed to describe the different performance appraisal fairness perceptions of employees in a hospitality organisation in Namibia. Using the organisational justice approach, a structured performance appraisal questionnaire was used to survey employee perceptions. The electronic survey was sent to N = 94 employees who were undergoing appraisal and results were analysed and presented using descriptive statistics. The study found that 55% of respondents agreed that the performance review system was effective to indicate how an employee performed during the review period. Only 29% of the respondents disagreed that the review system provided a fair measure of an employee's performance. The study also found that 63% of employees agreed that their supervisors were reliable. Results suggested that generally employees perceived the performance appraisal system as fair, and that satisfaction with the appraisal is guided by perceptions of fairness. The managerial implications of these findings are that the management of the hospitality organization will need to invest resources – both financial and human – to ensure that the organization reaffirms the performance appraisal method used by the organization and that it remains favoured by the employees.